REGIONAL DIFFERENCES OF POPULATION’S MIGRATION ACTIVITY IN THE CARPATHIAN REGION OF UKRAINE - TESLIUK, ROMAN; RUSHCHYSHYN, NADIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Analysis of the population’s migration activity in the Carpathian region of Ukraine is necessary to determine the spatial basis for the formation and development of territorial communities, development and implementation of demographic and socio-economic policy measures. The level of immigration to the Carpathian region from 2012 to 2020, annually exceeded the level of emigration. During this period, the urban settlements in the region are characterized by a stable migration increase (25 thousand people), while there was a migration reduction of the rural population of the region (by 4 thousand people). The increase is typical for Lviv and Ivano-Frankivsk regions, the negative migration balance is for Zakarpattia and Chernivtsi regions. The share of international migrants in migration flows in the Carpathian region is small, the population of Transcarpathia and Bukovina is more active in this regard.Interregional migration links are close between Lviv and Ivano-Frankivsk, Lviv and Zakarpattia, Ivano-Frankivsk and Chernivtsi regions. There is a noticeable reduction in the difference between the number of arrivals and departures, but in general the Carpathian region continues to be attractive for migration to residents of other country regions. In general, in 2016-2019, the population of the Carpathian region due to migration increased by 4 people per 10,000 population.The population’s migratory activity in the Carpathian region has a suburbanization character, which indicates the suburban areas attractive for living and working. Along with this, there is a significant leaching of human potential from mountainous areas, northern and north-eastern districts in Ivano-Frankivsk and Chernivtsi regions, industrial cities in the Carpathian region. The main threat to the development of the Carpathian region, caused by internal migration, is primarily the depopulation of some villages in the region, which is now manifested in the aging rural population. In the future, the unfavorable demographic situation in rural areas may lead to the decline of the local economy, social infrastructure and a general decline in the quality of life of residents.
Keywords: migration activity; Carpathian region of Ukraine; arrivals; departures; migration balance; stationary migration